A concise review of uncertainty analysis in metal machining. (2020) - Panda, Amlana; Kumar Sahoo, Ashok; Kumar, Ramanuj; Das, Diptikanta
Abstract: Of late, a significant progress has been performed in precision machining. Inaccuracies during the machine practice tend to generation of errors in orientation and position of machined component. Precision hard part turning augment tremendously in wide variety of industrial regions, particularly in roller bearing, automotive considered as flexible production approach. Precision hardly part turning has been impeded by uncertainties regarding process reliability and quality characteristics. The application of standard cutting tool sizes and shapes with Computerized Numerical Controlled machining systems can progress significantly geometric accuracy. Requirement of geometric accuracy, its use is limited by uncertainties regarding product quality and process reliability. With this regard, to curtail errors by ensuring proper optimal design is compensation strategies for better output characteristics. More precisely, this brief review pertains to different error analysis and uncertainty investigation and also its compensation strategies for better machining output and easy to is to implement in the machining shop floor. In addition, this review analysis will undeniably assist instrumentation engineers, machinist and practitioners who mainly deal with measuring equipments.